EKSPLOITASI TERHADAP KAUM SUBALTERN DALAM NOVEL PEREMPUAN KEMBANG JEPUN KARYA LAN FANG (SUATU TINJAUAN POSKOLONIAL GAYATRI SPIVAK) - Putri, Arfani Amelia; Mayong, Mayong; Faisal, Faisal (Fakultas Bahasa dan Sastra Indoensia, 2021)
Exploitation of the Subaltern in Novel Perempuan Kembang Jepun by Lan Fang (a Gayatri Spivak Postcolonial Review). This study aims to reveal forms of exploitation and violence against subalterns in Lan Fang’s novel Perempuan Kembang Jepun, seen from the postcolonial review of Gayatri Spivak. This research is qualitative descriptive. The data of this research are in the form of words, phrases, or sentences which indicate forms of exploitation and violence against subaltern characters in Lan Fang’s novel Perempuan Kembang Jepun. The results of the research are forms of exploitation of the subaltern during the colonial period, namely sexual and economic exploitation. As for the forms of violence experienced by subaltern characters in the novel, namely physical violence and psychological violence.